Analysis of Impulsive Buying Mechanism Through Hedonic Motivation, Emotion, and Online Trust - Muhammad Umar Al Faruq; Yolanda Masnita; Husna Leila Yusran (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the mechanisms underlying online impulse buying among Muslim women consumers of modest fashion in Indonesia by integrating psychological factors (hedonic motivation and positive emotions), economic factors (cashback), and cognitive–perceptual factors (online shopping attitude and perceived trust). Using Structural Equation Modeling (SEM) with AMOS, data were collected from 145 respondents. The constructs examined include Hedonic Motivation, Online Shopping Attitude, Online Impulse Buying, Cashback, Positive Emotions, and Perceived Trust. The results indicate that hedonic motivation significantly influences online shopping attitude (β = 0.642; p = 0.009), whereas online shopping attitude does not significantly influence impulse buying (p = 0.164). Cashback emerges as the strongest predictor of impulse buying (β = 0.777; p = 0.000), indicating that financial incentives operate as a form of controlled extrinsic motivation that directly stimulates spontaneous purchasing behaviour rather than shaping attitudinal evaluations. Positive emotions do not significantly affect online shopping attitude (p = 0.647), but they significantly influence perceived trust (β = 1.423; p = 0.000). Although perceived trust does not exert a significant direct effect on impulse buying, it functions as an indirect mechanism through which positive emotions contribute to impulsive purchasing behaviour, with an indirect effect value of 0.199. Theoretically, this study contributes to the literature by clarifying the distinct roles of intrinsic motivation and controlled extrinsic incentives within the framework of Self-Determination Theory (SDT) in explaining online impulse buying. Practically, the findings highlight the importance of affect-based marketing strategies and cashback programs as effective triggers of impulsive purchasing in modest fashion e-commerce.